CFTR Depletion Confers Hypersusceptibility to Mycobacterium fortuitum in a Zebrafish Model - Johansen, Matt D.; Kremer, Laurent (Frontiers in Cellular and Infection Microbiology, 2020)
The Mycobacterium fortuitum complex comprises several closely related species, causing pulmonary and extra-pulmonary infections. However, there is very limited knowledge about the disease pathogenesis involved in M. fortuitum infections, particularly due to the lack of suitable animal models. Using the zebrafish model, we show that embryos are susceptible to M. fortuitum infection in a dose-dependent manner. Furthermore, zebrafish embryos form granulomas from as early as 2 days post-infection, recapitulating critical aspects of mycobacterial pathogenesis observed in other pathogenic species. The formation of extracellular cords in infected embryos highlights a previously unknown pathogenic feature of M. fortuitum. The formation of large corded structures occurs also during in vitro growth, suggesting that this is not a host-adapted stress mechanism deployed during infection. Moreover, transient macrophage depletion led to rapid embryo death with increased extracellular cords, indicating that macrophages are essential determinants of M. fortuitum infection control. Importantly, morpholino depletion of the cystic fibrosis transmembrane conductance regulator (cftr) significantly increased embryo death, bacterial burden, bacterial cords and abscesses. There was a noticeable decrease in the number of cftr-deficient infected embryos with granulomas as compared to infected controls, suggesting that loss of CFTR leads to impaired host immune responses and confers hypersusceptiblity to M. fortuitum infection. Overall, these findings highlight the application of the zebrafish embryo to study M. fortuitum and emphasizes previously unexplored aspects of disease pathogenesis of this significant mycobacterial species.